Muscle structure predictors of vertical jump performance in elite male volleyball players: a cross-sectional study based on ultrasonography - Jiang, WeiDong; Chen, Chao; Xu, Yilin (Frontiers in Physiology, 2024)
Objective The objective of this investigation is to examine the contribution of key muscle groups in the lower limbs to vertical jumping performance in elite male volleyball players. Specifically, the study focuses on the rectus femoris (RF), vastus lateralis (VL), and lateral gastrocnemius (LG), as well as exploring differences between attack jump and other vertical jump types. Methods To achieve this, we employed B-mode ultrasound to evaluate the anatomical cross-sectional area (ACSA), muscle thickness (MT), pennation angle (PA), and fascicle length (FL) of the RF, VL, and LG in the participants. Fifteen elite male volleyball players were recruited as participants for this study. Jump heights were measured for four types of vertical jumps: attack jump (AJ), countermovement jump (CMJ), squat jump (SJ), and drop jump (DJ). We conducted regression analyses to assess whether the previously mentioned muscle structures could predict jump performance. Results Our findings reveal that the muscle structure of the RF does not exhibit any significant correlation with the height of any jump. However, VL-ACSA displays a significant and the most potent predictive effect on jump height for all four jump types (AJ: R2 = 0.32, p = 0.001; CMJ: R2 = 0.37, p = 0.005; SJ: R2 = 0.52, p = 0.001; DJ: R2 = 0.25, p = 0.021). Conversely, LG-FL only demonstrates a significant and stronger predictive effect on AJ jump height (R2 = 0.18, p = 0.009). Combining VL-ACSA, LG-FL, and training age through multiple linear regression analysis resulted in a highly significant model for predicting AJ jump height (F = 13.86, R2 = 0.73). Moreover, the model incorporating VL-ACSA and training age is also important for predicting CMJ, SJ, and DJ jump heights (F = 8.41, R2 = 0.51; F = 13.14, R2 = 0.63; F = 5.95, R2 = 0.41; respectively). Conclusion The muscle structure indicators in the lower limbs significantly predict jump performance among elite male volleyball players. However, different jump types are influenced by distinct indicators, particularly in the case of AJ, which is associated with LG-FL. This suggests that enhancing LG-FL may positively impact AJ ability, thereby emphasizing the importance of specificity in training. To optimize specialized jump performance in volleyball players, practitioners are advised to assess VL-ACSA and LG-FL and incorporate step-up and eccentric strength training targeting the calf muscles to yield considerable benefits.